Development of a new rain attenuation model for tropical location - Joseph Mom; Silas Soo Tyokighir; Gabriel Igwue (Institute of Advanced Engineering and Science, 2021)
This study proposes a new rain attenuation prediction model (RAM) based on the rain cell concept for tropical locations. The new model addresses the research gap in the international telecommunications union (ITU) model. Results obtained show that the proposed RAM predicted the possibility of signal across seven (7) out of thirteen (13) stations monitored. The predicted attenuation values were 18.3427 dB, 18.8106 dB, 18.3921 dB, 13.8062 dB, 20.8803 dB, 9.4519 dB, and 19.6018 dB for Jalingo, Jos, Makurdi, Mubi, Otukpo, Sokoto, and Abuja respectively. However, the RAM predicted outage across six stations with predicted attenuation values of 31.7040 dB, 26.8302 dB, 28.6635 dB, 29.6562 dB, 28.8827 dB, and 30.0614 dB for Akwa-Ibom, Benin, Donga, Port-Harcourt, Owerri, and Aba respectively. The proposed RAM hence suggests an additional Ku-band spot beam power of at least 331.97 watts for Nigeria's Nigerian communication satellite-1 (NIGCOMSAT-1R) Ku-band transponder to overcome the predicted attenuation across the six stations which recorded signal outage. The results from this study can be used by network engineers for the implementation of fade mitigation techniques (FMTs) such as site diversity and power control to aid telecommunication networks anticipate changes and allocate resources accordingly.